Dickens et Gaskell ou les difficultés mid-victoriennes à dire le vieillir - Marianne Camus (Cahiers Victoriens et Edouardiens)
The analysis of the representation of ageing will be limited to the midVictorian period and centred on the works of Charles Dickens and Elizabeth Gaskell. For if the wish to negate ageing is a constant feature of the century, the changes in social and cultural circumstances influence the forms taken by this negation or erasure. Old people are very present in the works of both novelists, but ageing as such is much harder to trace. The strategies used to avoid the representation of ageing—disguise, shifts, transmutation—will be looked into, as well as their relation with the spirit of the time. For fiction constructs as much as it reflects, not only the representation, but also the perception of ageing with its fears and its attempts at acceptance.